Fear and Loathing in the Classroom: Why Does Teacher Quality Matter? - Michael Insler; Alexander F. McQuoid; Ahmed S. Rahman; Katherine Smith (Institute of Labor Economics (IZA), 2021)
This work disentangles aspects of teacher quality that impact student learning and performance. We exploit detailed data from post-secondary education that links students from randomly assigned instructors in introductory-level courses to the students' performances in follow-on courses for a wide variety of subjects. For a range of first-semester courses, we have both an objective score (based on common exams graded by committee) and a subjective grade provided by the instructor. We find that instructors who help boost the common final exam scores of their students also boost their performance in the follow-on course. Instructors who tend to give out easier subjective grades however dramatically hurt subsequent student performance. Exploring a variety of mechanisms, we suggest that instructors harm students not by "teaching to the test," but rather by producing misleading signals regarding the difficulty of the subject and the "soft skills" needed for college success. This effect is stronger in non-STEM fields, among female students, and among extroverted students. Faculty that are well-liked by students – and thus likely prized by university administrators – and considered to be easy have particularly pernicious effects on subsequent student performance.
Keywords: I20; I21; I23; J24; 330; soft standards; sequential learning; teacher value-added; rate my professor; higher education